2020
DOI: 10.1093/ije/dyaa098
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of access to water from managed aquifer recharge systems for blood pressure and proteinuria in south-west coastal Bangladesh: a stepped-wedge cluster-randomized trial

Abstract: Background Drinking-water salinity has been associated with high blood pressure (BP) among communities in south-west coastal Bangladesh. We evaluated whether access to water from managed aquifer recharge (MAR)—a hydrogeological intervention to lower groundwater salinity by infiltrating rainwater into the aquifers—can reduce community BP. Methods We conducted a stepped-wedge cluster-randomized trial with five monthly visits be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 41 publications
(45 reference statements)
0
13
0
Order By: Relevance
“…High sweat flow may overwhelm the ability to reabsorb sodium from sweat. Therefore, sweating can potentially lead to decreased urinary sodium excretion, particularly for men, who may not have been fully acclimatized during the study [23]. Hence, bias due to sodium excretion in sweat may also have influenced our analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High sweat flow may overwhelm the ability to reabsorb sodium from sweat. Therefore, sweating can potentially lead to decreased urinary sodium excretion, particularly for men, who may not have been fully acclimatized during the study [23]. Hence, bias due to sodium excretion in sweat may also have influenced our analyses.…”
Section: Discussionmentioning
confidence: 99%
“…The first cohort study followed up 383 participants for two visits (742 person-visits) from southwest coastal Bangladesh during the wet season [21]. The second study was a population-based stepped-wedge randomized controlled trial in southwest coastal Bangladesh that followed up 1190 participants for five monthly visits (5745 person-visits) during the dry season [22,23]. The third cohort study followed up 293 participants from southwest coastal and 277 from non-coastal central Bangladesh for seven visits covering both wet and dry seasons (3547 person-visits data: 1773 from coastal and 1774 from non-coastal regions) [24].…”
Section: Data Sourcesmentioning
confidence: 99%
“… 20 The second study was a population-based stepped-wedge randomized controlled trial in southwest coastal Bangladesh that followed up 1190 participants for 5 monthly visits (5745 person-visits) to investigate the health effects of providing access to low-salinity groundwater. 21 , 22 The third cohort study followed up 293 participants from southwest coastal and 277 from noncoastal central Bangladesh for 7 visits (3547 person-visit data: 1773 from coastal and 1774 from noncoastal regions).…”
Section: Methodsmentioning
confidence: 99%
“…This is gaining increasing attention in countries such as Bangladesh with increasingly saline groundwater and polluted surface water, but feasibility systems require careful assessment (Naus et al 2021). Naser et al (2021) found that people consuming MAR water had higher urinary sodium and higher blood pressure than those continuing to rely on surface water sources and concluded that MAR should not be promoted as a routine water supply option. Such risk substitutions have been identified before in Bangladesh in relation to arsenic (Howard, 2003), but the risks with microbiological contamination tend to substantially outweigh those associated with chemical contaminants (Howard et al 2006a).…”
Section: Recommendations For Researchmentioning
confidence: 99%